2018
DOI: 10.1016/j.schres.2017.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Latent class cluster analysis of symptom ratings identifies distinct subgroups within the clinical high risk for psychosis syndrome

Abstract: The clinical-high-risk for psychosis (CHR-P) syndrome is heterogeneous in terms of clinical presentation and outcomes. Identifying more homogenous subtypes of the syndrome may help clarify its etiology and improve the prediction of psychotic illness. This study applied latent class cluster analysis (LCCA) to symptom ratings from the North American Prodrome Longitudinal Studies 1 and 2 (NAPLS 1 and 2). These analyses produced evidence for three to five subgroups within the CHR-P syndrome. Differences in negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 21 publications
0
21
1
Order By: Relevance
“…It is relevant to note that schizotypy, as a multidimensional and complex construct, allow us to identify these subgroups and to take into account the multiple expression of the psychosis phenotype (positive, negative and disorganization) rather than only the positive dimension of this phenotype (Pignon et al, ). Previous studies have examined the latent structure across all psychotic spectrum such as psychotic symptoms (Kendler et al, ; Pignon et al, ), schizotypal personality disorder (Fossati et al, ), subclinical psychosis symptoms (Ryan et al, ; Valmaggia et al, ), PLEs (Ahmed et al, ; Cella et al, ; Gale et al, ; Shevlin et al, ) and schizotypal traits (Cella et al, ; Denovan et al, ; Fonseca‐Pedrero, Gooding, Ortuño‐Sierra, & Paino, ; Fonseca‐Pedrero, Ortuno‐Sierra, et al, ; Hori et al, ; Tabak & Weisman de Mamani, ; Wang et al, ). Although there is heterogeneity in the measures used and the nature of the samples, previous studies conducted in adolescent population are clearly convergent with the results found in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is relevant to note that schizotypy, as a multidimensional and complex construct, allow us to identify these subgroups and to take into account the multiple expression of the psychosis phenotype (positive, negative and disorganization) rather than only the positive dimension of this phenotype (Pignon et al, ). Previous studies have examined the latent structure across all psychotic spectrum such as psychotic symptoms (Kendler et al, ; Pignon et al, ), schizotypal personality disorder (Fossati et al, ), subclinical psychosis symptoms (Ryan et al, ; Valmaggia et al, ), PLEs (Ahmed et al, ; Cella et al, ; Gale et al, ; Shevlin et al, ) and schizotypal traits (Cella et al, ; Denovan et al, ; Fonseca‐Pedrero, Gooding, Ortuño‐Sierra, & Paino, ; Fonseca‐Pedrero, Ortuno‐Sierra, et al, ; Hori et al, ; Tabak & Weisman de Mamani, ; Wang et al, ). Although there is heterogeneity in the measures used and the nature of the samples, previous studies conducted in adolescent population are clearly convergent with the results found in this study.…”
Section: Discussionmentioning
confidence: 99%
“…It is relevant to note that schizotypy, as a multidimensional and complex construct, allow us to identify these subgroups and to take into account the multiple expression of the psychosis phenotype (positive, negative and disorganization) rather than only the positive dimension of this phenotype (Pignon et al, 2018). Previous studies have examined the latent structure across all psychotic spectrum such as psychotic symptoms (Kendler et al, 1998;Pignon et al, 2018), schizotypal personality disorder (Fossati et al, 2001), subclinical psychosis symptoms (Ryan et al, 2017;Valmaggia et al, 2011), PLEs (Ahmed et al, 2012;Cella et al, 2011;Gale et al, 2011;Shevlin et al, 2007) Another important issue involves the clinical implications of these homogeneous groups of psychosis liability. First, the literature on schizotypy suggest that anhedonia is the most consistently found predictor of conversion to psychosis Flückiger et al, 2016;Radua et al, 2018); thus it could be hypothesized that, in a longitudinal study, the "Social Disorganization schizotypy" group would entail higher conversion rates than the other groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a similar study, Ryan et al. () found three clusters of at‐risk individuals: (1) perceptual abnormalities (mainly characterized by the presence of hallucinations, distortions, illusions, and low levels of negative symptoms), (2) disorganized speech (with mainly negative and disorganization symptoms), and (3) a cluster distinguished by impairment in personal hygiene. Furthermore, the disorganized speech cluster showed the highest conversion rate to psychosis.…”
Section: Introductionmentioning
confidence: 92%
“…Latent class analysis classifies population heterogeneity into categorical groups of homogeneous individuals which may have implications for classification (i.e., diagnosis), prognosis (i.e., longitudinal course), and treatment (i.e., propensity to respond to different treatments) ( 17 ). Latent class analysis has been increasingly applied in psychiatry to identify subgroups of patients or clinical markers that may have clinical utility but which are obscured by more traditional methods of analysis, such as pairwise group comparisons that presuppose diagnostic structures and their relationship to clinical characteristics ( 18 20 ). In latent class analysis, the presence of a group of people who are homogenous in their symptom profile should present as a single latent class.…”
Section: Introductionmentioning
confidence: 99%